2020
DOI: 10.1002/aqc.3508
|View full text |Cite
|
Sign up to set email alerts
|

Surveys of recreational anglers reveal knowledge gaps and positive attitudes towards manta ray conservation in Florida

Abstract: South Florida has a significant number of recreational anglers, and some shore‐based fishing sites overlap with habitat for juvenile manta rays. Although manta rays are prohibited from harvest in Florida, they are frequently seen foul‐hooked or entangled in fishing line. Recreational anglers (n = 198) were surveyed at piers and inlet jetties in Palm Beach County, Florida, USA to assess their knowledge of and actions and attitudes towards manta rays. Analysis of the responses revealed that while most anglers co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 49 publications
(61 reference statements)
0
11
0
Order By: Relevance
“…Fishing line entanglement was documented on 27% of individuals in southeast Florida, along with vessel strike injury and rapid wound healing 26 . Outreach focused on preventing recreational fishery interactions with manta rays, encouraging use of environmentally-friendly tackle, and fostering engagement with anglers as citizen scientists is needed in southeast Florida 106 . Our SDMs will allow managers to more effectively time and coordinate management strategies, including targeted outreach efforts and developing spatiotemporal ‘windows’ for action agencies to reduce the risk of manta interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Fishing line entanglement was documented on 27% of individuals in southeast Florida, along with vessel strike injury and rapid wound healing 26 . Outreach focused on preventing recreational fishery interactions with manta rays, encouraging use of environmentally-friendly tackle, and fostering engagement with anglers as citizen scientists is needed in southeast Florida 106 . Our SDMs will allow managers to more effectively time and coordinate management strategies, including targeted outreach efforts and developing spatiotemporal ‘windows’ for action agencies to reduce the risk of manta interactions.…”
Section: Discussionmentioning
confidence: 99%
“…and value healthy shark populations (Shiffman et al, 2014), and casual anglers who may not otherwise be aware of sawfish conservation (e.g., for discussion of Florida shorebased angler knowledge about manta conservation, see Pate et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence for support of conservation by some anglers, even when there is conflict between anglers and the species of conservation concern (e.g., support for conservation of sharks despite depredation) (Coulson et al, 2022). One study found anglers support conservation of manta rays, another threated species of ray, which like sawfish are unlikely to be in direct conflict with anglers (Pate et al, 2021). With this in mind, we believe that angler support for conservation of sawfish is very likely, because sawfish-angler conflict is limited, and anglers are often excited about encountering sawfish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fishing piers are an important source of recreational bycatch and entanglement for avian, fish, and other megafaunal species, such as sea turtles (Donnelly-Greenan et al 2019, Cook et al 2020, Pate et al 2021. In fact, recreational bycatch of sea turtles has been documented at fishing piers along the US Gulf of Mexico (GoMx) by STSSN for > 40 yr (Canon et al 1994, STSSN unpubl.…”
Section: Introductionmentioning
confidence: 99%